3-D Printed Planar Dielectric Linear-to-Circular Polarization Conversion and Beam-Shaping Lenses Using Coding Polarizer - Zhu, Jianfeng; Yang, Yang; McGloin, David; Rajasekharan Unnithan, Ranjith; Li, Shufang; Liao, Shaowei; Xue, Quan (IEEE transactions on antennas and propagation, 2020)
This article presents a new linear-to-circular polarization conversion coding unit, on which two new kinds of beam-shaping lenses are proposed. First, under periodic boundary conditions, a linear-to-circular polarization conversion coding unit is introduced, which introduces the necessary phase delay by adjusting its geometrical parameters. The phase delay ranges from 0° to 360° and is discretized into 3 bit coding units corresponding to specific delays. Second, by properly arranging the coding units, a high-gain circularly polarized (CP) lens is proposed. The lens achieves linear-to-circular polarization conversion and beam collimation in the transmission mode simultaneously with a planar configuration, which is different from counterparts that place a lens atop of a polarizer. Furthermore, the coding units are used to form Wollaston-prism-like and Rochon-prism-like planar CP beam-shaping lenses, which split the beams with different polarizations into right- and left-handed components. These beams can be controlled independently. Prototypes working at 30 GHz band are designed, fabricated, and measured to verify the idea.